Cuantificación de la huella hídrica del cultivo de arroz en dos zonas productoras de Perú. Arroz de riego en Perú competitivo e eficiente en el uso de agua mediante agricultura climáticamente inteligente - Sierra, Leidi; Romero Sánchez, Miguel Antonio (International Center for Tropical Agriculture, 2020)
As the freshwater becomes a more essential and scarce resource, indicators have been arisen to measure water consumption. This has helped to warn about the use of this resource in different production sectors. Thus, several organizations have converged in a methodology for water footprint estimation. The water footprint is a sustainability indicator, which allows determining the agro-livestock impact on the environment. The impact assessment is carried out through the freshwater quantification used directly or indirectly in an agricultural production process. This study pretends to determine the water footprint for rice production in four different Peru's localities. The methodology was taken from the "The Water Footprint Assessment Manual", which sets the global standards for water consumption gauging.